Dynamic Characteristic Study of Supercritical CO2 Recompression Brayton Cycle System - Zhu, Qinghui; Han, Ruiyan; Yang, Siyuan; Zhang, Bo; Yang, Zhuqiang (Frontiers in Energy Research, 2022)
The supercritical carbon dioxide (SCO2) Brayton cycle has been regarded as the main development direction of future nuclear power generation by more and more scholars, due to its high environmental efficiency and high thermoelectric conversion rate. However, due to fluctuations in the operation of the primary loop of the system with nuclear energy, parameters such as the power of the heat source and the mass flow of the working medium in the system will change, which will affect the dynamic performance and operation of the SCO2 Brayton cycle system. Therefore, it is necessary to study the dynamic response of the system performance under disturbance conditions, analyze the operating characteristics of the SCO2 Brayton cycle system. In this paper, a comprehensive dynamic model of SCO2 recompression Brayton cycle, which analyzes the response curves of critical parameters under the disturbance of heat source heating power and system mass flow rate, is accurately developed based on Simulink software. In order to verify the validity of the proposed model, the simulation results are compared with the experimental results conducted by Sandia Laboratory under the same conditions. The results show that the model has high accuracy, and can reflect the dynamic response of system performance under parameter perturbation. In this paper, the closed-loop simulation is innovatively performed to show the dynamic response to step-change in the heat source power and mass flow rate. And the thermal efficiency is about 31.85%, when the system operates stably at the design point of working condition. If a disturbance is applied to the system, the temperature change will be mainly concentrated near the heat source of the cycle, and the change near the precooler will be relatively small. The change of the heat source power will lead to a large monotonic variation of cycle efficiency. By contrast, an inflection point in cycle efficiency will be resulted in by changing the system mass flow rate. The results of this paper would provide good approaches for the design, control, and improvement of the SCO2 Brayton cycle.